Ultraflexible Organic Photovoltaics: Nanograting Structured Ultrathin Substrate for Ultraflexible Organic Photovoltaics (Small Methods 3/2020). Issue 3 (6th March 2020) - Takakuwa, Masahito; Heo, Soo Won; Fukuda, Kenjiro; Tajima, Keisuke; Park, Sungiun; Umezu, Shinjiro; Someya, Takao
Abstract : In article number 1900762 by Kenjiro Fukuda, Shinjiro Umezu, Someya Takao, and co‐workers, the fabrication of ultraflexible organic photovoltaics on nanostructured substrates is reported. The organic photovoltaics have a high power conversion efficiency and a low dependence on incident light angle. By combining nanograting structures in other layers, the organic photovoltaics further improve power conversion efficiency.